État des lieux de la recherche sur les formations ouvertes et à distance en Afrique subsaharienne francophone - Béché Emmanuel (Centre National d'Enseignement à Distance, 2016)
This article describes the literature review on distance learning in francophone Sub-Saharan Africa. The state of research on this question shows many topics, including the supporting motives for the creation of ODL and their potential, the successes, difficulties and issues linked to their implementation, the representations, motivations and identities of students, and their historical and cooperative aspects. While most of the studies are descriptive or exploratory, others are however critical. Beyond this state, many perspectives are to be explored, mainly those related to practices, experiences and transformations that take place within ODL